High-frequency vegetation and climatic changes during the Lateglacial inferred from the Lapsou pollen record (Cantal, southern Massif Central, France). (30th October 2022) - Duprat-Oualid, Fanny; Bégeot, Carole; Peyron, Odile; Rius, Damien; Millet, Laurent; Magny, Michel
Abstract: The Lateglacial period is marked by strong changes in environment and climate in Europe, associated to the different steps of the deglaciation. This paper aims to reconstruct the vegetation and climate changes from the deglaciation to the early Holocene (15.2–10.8 ka cal BP) in Western Europe. Pollen investigations are performed at a centennial resolution on a sedimentary core from the Lapsou peat bog (Cantal, France). The chronology is well constrained from three radiocarbon dates and a double tephra layer. The pollen record and quantitative climate reconstructions evidence strong changes associated with the Lateglacial period, in agreement with the regional vegetation and climate dynamics. At the onset of Lateglacial Interstadial (14.5–14.1 ka cal BP), a Juniperus - Betula succession is attributed to the Bølling. Associated climate reconstructions indicate a winter warming of 10 °C and precipitations above 1000 mm. A development of Pinus forests is then evidenced for the Allerød, for which rather constant warm conditions and lower precipitations (drop of 200 mm) are reconstructed. A two-phase pattern characterizes the Younger Dryas (12.6–11.5 ka cal BP): after a first phase with rather constant vegetation and climate conditions compared to the Allerød, a more steppic vegetation developed from 12.2 ka cal BP, indicating a marked cooling and a pronounced aridity (precipitations around 400 mm). Finally, the reconstruction of a cool deciduous forest dominated by Betula and temperate climate conditions defines the early Holocene. A comparison with chironomid-inferred reconstructions of July temperature from the close La Roustière site allows to support pollen-inferred climate quantifications, also showing the interest of applying multi-proxy approach in palaeo-environmental studies.